Pemodelan dan Simulasi Urutan Pengelasan Bilah Roda Traktor Berbasis Metoda Elemen Hingga - Suryadiwansa Harun; Yanuar Burhanuddin (Institute of Research and Community Outreach, Petra Christian University, 2010)
This paper discusses the modelling and simulation of welding process based on the finite element method (FEM) in order to predict the welding distortion of tractor wheel blades. Two FEM modellings are needed to obtain the welding distortion models, namely thermal and elasto-plastic. The effect of welding thermal is assumed as tendon force and to be used as input of the analysis of elasto-plastic modelling. Welding distortion simulation results were verified using the experimental data. The verification results have shown similar shape of the welding deformation between simulations and experimental. Also, deviation value of displacement distortion between simulation and experimental is small. Hence, the simulation of welding deformation modelling using thermal elasto-plastic FEM can be used to predict the welding distortion of tractor wheel blades. Based on simulation results, the shape of radial and axial displacement distortion due to welding the blade with serial sequence was larger than that of the shape distortion due to welding of the blade with a recommended sequence. After welding simulation of those of 16 wheels tractor blades, the predicted value of displacement distortion due to welding of the blade with serial sequence is equal to 3,393mm, which was larger than that of 1,440mm due to welding of the blade with recommended sequence.